Compact differential bandpass filter with a narrow notched band using APCL structure suitable for UWB application. Issue 9 (September 2015) - Amirian, Mohsen; Karimi, Gholamreza; Lalbakhsh, Ali; Bayati, Mohammad-sajad
Abstract A compact differential band pass filter with asymmetric parallel-coupled lines (APCL) and center frequency of 5.6 GHz is proposed in this paper. The APCL suppresses unwanted RFID signals by introducing a fully tunable notched band at 6.8 GHz. By combining the concept of transmission matrix with modal analysis and extracting a novel model for symmetric three parallel coupled lines (SPCL), role of each resonant frequency is clearly explained. Measurement results in the differential mode show a pass band from 3.1 to 8.1 GHz and a wide stop band from 9.1 to 16 GHz with attenuation of more than 20 dB. In addition, S21 in common mode is lower than −10.5 dB over the pass band.